RESULTS OF ACUTE LYMPHOBLASTIC LEUKEMIA TREATMENT WITH INTENSIVE CHEMOTHERAPY IN CHILDREN IN ST.-PETERSBURG: RETROSPECTIVE EVALUATION OF TWO VERSIONS OF COALL-92 PROTOCOL - E.G. Boichenko; E.M. Petrova; I.A. Garbusova; Yu.A. Nikitina; T.N. Kulakova; T.A. Makarova; M.B. Belogurova; G.G. Radulesku; T.D. Viktorovich; E.D. Chavpetsova; L.I. Shats; G.I. Uleiskaya; et al. ("Paediatrician" Publishers LLC, 2011)
Regardless the success gained in treatment of acute lymphoblastic leukaemia, several problems still remain to be solved, such as: overcoming primary drug resistance and minimizing the amount of relapses as well as decreasing of chemotherapy toxicity without detriment to the final outcome of the treatment. Development of an optimal chemotherapeutical strategy still remains a hot issue. Objective: to evaluate an efficacy of two modifications of German protocol COALL-92 in treatment of ALL in children in St.-Petersburg. Methods: the retrospective analysis of results of treatment in patients under 18 years old with ALL was performed. The diagnosis was confirmed according to international criteria. The treatment was performed via protocols PECO-92 and COALL-St.-Petersburg-92. Results: 438 initial patients with ALL were treated in St.-Petersburg clinics during the period from 01.01.1993 to 01.01.2007. At the time of analysis the probability of event-free survival (pEFS) was 60% in group of PECO-92 protocol and 70% - in COALL group (plog-rank = 0,048), probability of relapse-free survival (рRFS) was 65 and 74% (plog-rank = 0,002), probability of overall survival was (pOS) 78 and 70%, correspondingly (plog-rank = 0,079). Conclusion: inclusion of protocol treatment in practice of St.-Petersburg hospitals resulted in significant improvement of treatment results in children with ALL. The problem of both versions of COALL protocol is high rate of postremission mortality due to high toxicity of intensive stage if chemotherapy. Key words: children, acute lymphoblastic leukemia, intensive chemotherapy. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 33-42)